Ectopic taste receptors in animal physiology: evolutionary conservation and functional diversification - Chen, Kejin; Liang, Xinyu; Yi, Hongyu; Yu, Guixiang; Wu, Qi (Frontiers in Cell and Developmental Biology, 2025)
Taste perception is crucial for animals to assess food’s nutritional value while avoiding toxic substances. Recent decades have unveiled the presence of taste receptors beyond the oral cavity, expressed in diverse non-gustatory tissues including gastrointestinal, cardiovascular, reproductive, and neural tissues. These ectopically expressed taste receptors are implicated in a multitude of physiological processes such as the regulation of hormone secretion, nutrient sensing and digestive processes, pathogen defense, and modulation of locomotor abilities. Moreover, these receptors present potential pharmacological targets for therapeutic interventions in diseases related to the respiratory, digestive, and cardiovascular systems. In this review, we summarize the recent advances in understanding the distribution and functions of extraoral taste receptors in mammals, teleosts, insects, and nematodes, emphasizing the commonalities and variations among different species. The emerging paradigm positions taste receptors as polymodal sensors integrating environmental cues with physiological homeostasis beyond their canonical gustatory functions, offering new perspectives on sensory system evolution and organismal adaptation.